Methodology Of Teaching Medical Terms And Using Tasks That Develop Qualification Skills (Global Scientific Review, 2023)
In this article, it is explained about the acquisition of professional skills in the study of medical terminology in medicine, as well as the application and formation of this knowledge in practice, and the methods of teaching medical terms to students